Process intensification in continuous flow organic synthesis with enabling and hybrid technologies - Grillo, Giorgio; Cintas, Pedro; Colia, Mariachiara; Calcio Gaudino, Emanuela; Cravotto, Giancarlo (Frontiers in Chemical Engineering, 2022)
Industrial organic synthesis is time and energy consuming, and generates substantial waste. Traditional conductive heating and mixing in batch reactors is no longer competitive with continuous-flow synthetic methods and enabling technologies that can strongly promote reaction kinetics. These advances lead to faster and simplified downstream processes with easier workup, purification and process scale-up. In the current Industry 4.0 revolution, new advances that are based on cyber-physical systems and artificial intelligence will be able to optimize and invigorate synthetic processes by connecting cascade reactors with continuous in-line monitoring and even predict solutions in case of unforeseen events. Alternative energy sources, such as dielectric and ohmic heating, ultrasound, hydrodynamic cavitation, reactive extruders and plasma have revolutionized standard procedures. So-called hybrid or hyphenated techniques, where the combination of two different energy sources often generates synergistic effects, are also worthy of mention. Herein, we report our consolidated experience of all of these alternative techniques.